2020
DOI: 10.3390/ijerph17176035
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic Brings a Sedentary Lifestyle in Young Adults: A Cross-Sectional and Longitudinal Study

Abstract: The coronavirus disease 2019 (COVID-19) pandemic continues to pose profound challenges to society. Its spread has been mitigated through strategies including social distancing; however, this may result in the adoption of a sedentary lifestyle. This study aimed to investigate: 1) physical activity (PA) levels, sedentary behavior (SB), and sleep in young adults during the COVID-19 epidemic, and 2) the change in these behaviors before and during the pandemic. A total of 631 young adults (38.8% males) aged between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
201
3
22

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(239 citation statements)
references
References 26 publications
13
201
3
22
Order By: Relevance
“…While sleep quality has been frequently investigated, results have not always been consistent. In China, Wang and colleagues found that 75% of 2289 individuals isolated at home rated their sleep as very good [ 11 ], but a smaller prospective study found that 37% of a sample of young Chinese adults reported a worsening of their sleep quality during the pandemic [ 12 ]. Studies conducted in other countries have demonstrated that lockdown could either lead to an increase in the amount of time spent in bed [ 13 , 14 ], with good sleep efficiency [ 13 ] or associated with sleep disorders [ 15 , 16 ] and disruption of one’s habitual circadian rhythm [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…While sleep quality has been frequently investigated, results have not always been consistent. In China, Wang and colleagues found that 75% of 2289 individuals isolated at home rated their sleep as very good [ 11 ], but a smaller prospective study found that 37% of a sample of young Chinese adults reported a worsening of their sleep quality during the pandemic [ 12 ]. Studies conducted in other countries have demonstrated that lockdown could either lead to an increase in the amount of time spent in bed [ 13 , 14 ], with good sleep efficiency [ 13 ] or associated with sleep disorders [ 15 , 16 ] and disruption of one’s habitual circadian rhythm [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive Internet use is sometimes viewed as an asocial behavior that is linked with mood disorders, but during the COVID-19 crisis, the Internet significantly helped people socialize (Banjanin et al 2015;Chen and Peng 2008;Marcinkowski et al 2010). University students relied on online tools to communicate with their peers, build and maintain relationships with friends, and remain socially connected (Cain 2008;Martínez-Alemán and Wartman 2008;Park 2010;Swist et al 2015;Wyn et al 2005). The virtual environment, online public space and online communities completely replaced physical public spaces during the pandemic (Hampton et al 2010;Király et al 2020;Li 2010;Prakash et al 2020).…”
Section: Psychological Well-being and The Social And Physical Activitmentioning
confidence: 99%
“…Around the world, COVID-19 quickly disrupted everyday life ( Sundarasen et al, 2020 ; Zhang W.-R. et al, 2020 ; Zheng et al, 2020 ), causing significant physical harm for a large proportion of the community ( Sibley et al, 2020 ). With the goal of curtailing the spread of the virus, many governments implemented strict quarantine, and spatial distancing measures.…”
Section: Introductionmentioning
confidence: 99%